PEMBERDAYAAN MASYARAKAT GAMPONG PANGO DEAH MELALUI INOVASI SABUN PEMBERSIH LANTAI ANTIBAKTERI BERBASIS MINYAK NILAM DAN SEREH - Fakri, Fajar; Nasution, Muhammad Amin; Asyifa, Cut Nella; Iryana, Mirdha; Muhni, Akmal; Afra, Mauliza; Sandrina, Syura; Humaira, Zaura (Universitas Mataram, 2025)
Patchouli oil and citronella oil are Aceh’s leading commodities that produce essential oils with various benefits, including natural antibacterial properties. However, their utilization in household products remains limited, while most communities still rely on chemically based floor cleaners at relatively high prices. In response to this potential, a community service program was conducted in Pango Deah Village by empowering beneficiaries of the Family Hope Program (PKH) to innovate in producing antibacterial floor cleaning soap based on patchouli and citronella oils. The activities included socialization on household hygiene, technical training on soap production, hands-on practice through a learning-by-doing approach, and evaluation using pre-test and post-test assessments. The evaluation results showed an increase in the average score from 78.50% to 99.00% after the training, indicating a significant improvement in participants’ understanding and practical skills. All participants (100%) expressed high satisfaction with the content, methods, and overall benefits of the program. The resulting floor cleaning soap exhibited a distinctive aroma of patchouli and citronella, as well as good product stability, making it a promising environmentally friendly household product with market potential. Participants’ enthusiasm was demonstrated by their intention to further develop the product as a home-based business. This program is expected to enhance community skills, promote economic independence, and encourage the sustainable utilization of local resources.